(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
This article analyzes infrastructure reconstruction and economic revitalization in Azerbaijan’s liberated territories, with a focus on transport, energy, agriculture, investment, and ecological restoration. The study highlights green energy and smart city initiatives as key drivers of sustainable post-conflict development, demonstrating Azerbaijan’s reconstruction model as a significant example of regional recovery and long-term economic sustainability.